Effect of Ketamine on Limbic GABA and Glutamate: A Human In Vivo Multivoxel Magnetic Resonance Spectroscopy Study - Silberbauer, Leo R.; Spurny, Benjamin; Handschuh, Patricia; Klöbl, Manfred; Bednarik, Petr; Reiter, Birgit; Ritter, Vera; Trost, Patricia; Konadu, Melisande E.; Windpassinger, Marita; Stimpfl, Thomas; Bogner, Wolfgang; et al. (Frontiers in Psychiatry, 2020)
Introduction: Converging evidence suggests that ketamine elicits antidepressant effects via enhanced neuroplasticity precipitated by a surge of glutamate and modulation of GABA. Magnetic resonance spectroscopic imaging (MRSI) illustrates changes to cerebral glutamate and GABA immediately following ketamine administration during dissociation. However, few studies assess sub-acute changes in the first hours following application, when ketamine’s antidepressant effects emerge. Moreover, ketamine metabolites implicated in its antidepressant effects develop during this timeframe. Thus, this study aimed to investigate sub-acute changes in cerebral Glx (glutamate + glutamine), GABA and their ratio in seven brain regions central to depressive pathophysiology and treatment. Methods: 25 healthy subjects underwent two multi-voxel MRS scans using a spiral encoded, MEGA-edited LASER-localized 3D-MRSI sequence, at baseline and two hours following intravenous administration of racemic ketamine (0.8 mg/kg bodyweight over 50 minutes). Ketamine, norketamine and dehydronorketamine plasma levels were determined at routine intervals during and after infusion. Automated region of interest (ROI)-based quantification of mean metabolite concentration was used to assess changes in GABA+/total creatine (tCr), Glx/tCr and GABA+/Glx ratios in the thalamus, hippocampus, insula, putamen, rostral anterior cingulate cortex (ACC), caudal ACC and posterior cingulate cortex. Effects of ketamine on neurotransmitter levels and association with ketamine- and metabolite plasma levels were tested with repeated measures analyses of variance (rmANOVA) and correlation analyses, respectively. Results: For GABA+/tCr rmANOVA revealed a measurement by region interaction effect (puncorr < 0.001) and post-hoc pairwise comparisons showed a reduction in hippocampal GABA+/tCr after ketamine (pcorr = 0.02). For Glx/tCr and GABA+/Glx neither main effects of measurement nor measurement by region interactions were observed (all puncorr > 0.05). Furthermore, no statistically significant associations between changes in any of the neurotransmitter ratios and plasma levels of ketamine, norketamine or dehydronorketamine were observed (pcorr > 0.05). Conclusion: This study provides evidence for decreased hippocampal GABA+/tCr ratio two hours following ketamine administration. As MRS methodology measures total levels of intra- and extracellular GABA, results might indicate drug induced alterations in GABA turnover. Our study in healthy humans suggests that changes in GABA levels, particularly in the hippocampus, should be further assessed for their relevance to ketamine´s antidepressant effects.